Sudden infant death syndrome: bed sharing with mothers who smoke. Issue 2 (1st February 2003) - James, C; Klenka, H; Manning, D
Abstract : Aim: To examine the sleeping arrangements of sudden infant death syndrome (SIDS) cases on the Wirral. In particular to determine the prevalence of bed sharing with mothers who smoke, a known risk factor for SIDS. Methods: Retrospective study of postmortem determined cases of SIDS from 1995 to 2000 on the Wirral peninsula (population 350 000, 3500 annual births). Ambulance crew reports, case notes, health visitor reports, postmortem reports, and case discussion records were studied for each case. Results: There were 25 cases of SIDS in the postneonatal age group over the six year period. In nine cases the baby was bed sharing with the mother, of whom seven were smokers. Five of these mothers reported using alcohol or illicit drugs on the night of their infant's death. In two further cases the baby slept on a sofa with a parent. Conclusions: Bed sharing and smoking remain important risk factors for SIDS. Mothers should be advised ante- and postnatally of this combination of risk factors. Such advice should also include a recommendation not to sleep with their baby if under the influence of alcohol or illicit drugs, and never to sleep on a sofa with their baby. All "Child Health Record" books given to parents on the Wirral now include this advice. "Reduce the Risk" advice leaflets given to parents pre- and postnatally also now carry the recommendation, and health visitors and midwives have been educated with respect to these additions.